A compact planar low-energy-gap molecule with a donor–acceptor–donor nature based on a bimetal dithiolene complex. Issue 87 (14th September 2015) - Hayashi, Mikihiro; Otsubo, Kazuya; Kato, Tatsuhisa; Sugimoto, Kunihisa; Fujiwara, Akihiko; Kitagawa, Hiroshi
Abstract : We prepared a compact, planar, low-energy-gap molecule with donor–acceptor–donor (D–A–D) nature for the first time based on a bimetal dithiolene complex. Abstract : We present the first report of a compact, planar and low-energy-gap molecule based on a π-conjugated bimetal system comprising a tetrathiooxalate (tto ) skeleton. The observed low HOMO–LUMO energy gap (1.19 eV) is attributed to its donor–acceptor–donor (D–A–D) nature because thetto skeleton acts as an electron acceptor as well as a tiny and noninnocent bridging moiety.